TLR7 mediated viral recognition results in focal type I interferon secretion by dendritic cells. Issue 1 (December 2017) - Saitoh, Shin-Ichiroh; Abe, Fumiko; Kanno, Atsuo; Tanimura, Natsuko; Mori Saitoh, Yoshiko; Fukui, Ryutaro; Shibata, Takuma; Sato, Katsuaki; Ichinohe, Takeshi; Hayashi, Mayumi; Kubota, Kazuishi; Kozuka-Hata, Hiroko; et al.
Abstract Plasmacytoid dendritic cells (pDC) sense viral RNA through toll-like receptor 7 (TLR7), form self-adhesive pDC–pDC clusters, and produce type I interferons. This cell adhesion enhances type I interferon production, but little is known about the underlying mechanisms. Here we show that MyD88-dependent TLR7 signaling activates CD11a/CD18 integrin to induce microtubule elongation. TLR7+ lysosomes then become linked with these microtubules through the GTPase Arl8b and its effector SKIP/Plekhm2, resulting in perinuclear to peripheral relocalization of TLR7. The type I interferon signaling molecules TRAF3, IKKα, and mTORC1 are constitutively associated in pDCs. TLR7 localizes to mTORC1 and induces association of TRAF3 with the upstream molecule TRAF6. Finally, type I interferons are secreted in the vicinity of cell–cell contacts between clustered pDCs. These results suggest that TLR7 needs to move to the cell periphery to induce robust type I interferon responses in pDCs. Antiviral immune responses involve clustering of plasmacytoid dendritic cells (pDC) in response to endosomal TLR7-mediated sensing of viral RNA. Here the authors show the GTPase Arl8b controls translocation of TLR7+ endosomes to the periphery of the cell via microtubule interactions, thus enabling pDC clustering and type I interferon production.